PRODUKSI KARKAS DAN PERSENTASE LEMAK ABDOMINAL ITIK TEGAL JANTAN DENGAN SISTEM PEMELIHARAAN INTENSIF DAN SEMI INTENSIF DI KTT BULUSARI PEMALANG - W.A. Ramadhana; D. Sunarti; T.A. Sarjana (Jurnal Ilmiah Peternakan Terpadu, 2019)
The aims of this study was to determine the differences in intensive and semi-intensive rearing systems on body weight, carcass weight, percentage of abdominal fat, and relative income for producing carcasses of Male Tegal duck in KTT Bulusari, Pemalang. The study was conducted on April - May 2018, in Bulusari farmer group’s farm at Bulu Village, Petarukan, Pemalang District, and Central Java. The material used in this study was male Tegal ducks from 10 farmers at the Bulu Village with the object were in Petarukan Sub-district consisting of 5 semi-intensive and 5 intensive rearing systems. Tegal duck is maintained for 42 days. This research was a quantitative descriptive research that interprets a data from a research sample analyzed by the Mann-Whitney test. The results showed that male Tegal ducks that were kept intensively in Bulusari farmer group’s farm had higher body weight, carcass weight, percentage of abdominal fat and relative income than semi intensive reared duck (P < 0,05). The conclusion of this study was intensively reared ducks had higher carcass production and percentage of abdominal fat than semi intensively reared ducks.